Interlanguage effect on writing anxiety in a foreign language context - Tülin Türnük; Selami Aydın (Literacy Trek, 2020)
Both writing anxiety and interlanguage errors may have adverse effects on writing achievement and performance among English as a foreign language (EFL) learners. However, whether writing anxiety and interlanguage error are related or not remains an unanswered question. This study aims to investigate whether interlanguage errors relate to writing anxiety in the EFL learning context. The sample group of the study consists of 106 Turkish EFL learners studying English at the preparatory school of a state university. After administering a background questionnaire and a survey that contained 22 items that aimed to determine the level of writing anxiety among students, students' written products were used to find and categorize interlanguage errors. The frequencies, mean scores, and standard deviations were calculated to show the levels of interlanguage errors and writing anxiety. Then, the relationship between writing anxiety and interlanguage errors was analyzed by using ANOVA. The results indicated that EFL learners who have more interlanguage errors experience writing anxiety at higher levels. In light of the findings, the study provides some practical recommendations for target groups.